Foundations of robotics : a multidisciplinary approach with Python and ROS - Herath, Damith; St. Onge, David (Singapore : Springer, 2022)
This open access book introduces key concepts in robotics in an easy to understand language using an engaging project-based approach. It covers contemporary topics in robotics, providing an accessible entry point to fundamentals in all the major domains. A section is dedicated to introducing programming concepts using Python, which has become a language of choice in robotics and AI. The book also introduces the reader to the Robot Operating System (ROS), the ubiquitous software and algorithmic framework used by researchers and the industry. The book provides an inspired, up-to-date and multidisciplinary introduction to robotics in its many forms, including emerging topics related to robotics on Machine Learning, ethics, Human-Robot Interaction, and Design Thinking. The book also includes interviews with industry experts, providing an additional layer of insight into the world of robotics. The book is made open access through the generous support from Kinova Robotics. The book is suitable as an undergraduate textbook in a relevant engineering course. It is also suitable for students in art and design, high school students, and self-learners who would like to explore foundational concepts in robotics.
PART I: Contextual Design -- Chapter 1 - Genealogy of artificial beings: from ancient automata to modern robotics (Nicolas Reeves and David St-Onge) -- Chapter 2 - Teaching and learning robotics: A pedagogical perspective(Eleni Petraki and Damith Herath) -- Chapter 3 - Design Thinking: from Empathy to Ideation(Fanke Peng).-Chapter 4 - Software building blocks: From Python to Version control (Damith Herath, Adam Haskard and Niranjan Shukla) -- Chapter 5 - The Robot Operating System (ROS1&2): programming paradigms and deployment(David St-Onge and Damith Herath) -- Chapter 6 - Mathematical building blocks: From geometry to quaternions to Bayesian(Rebecca Stower, Bruno Belzile and David St-Onge).-PART II: Embedded Design -- Chapter 7 - What makes robots? Sensors, Actuators and Algorithms (Jiefei Wang and Damith Herath) -- Chapter 8 - Mobile robots: Controlling, Navigating and path planning( Jiefei Wang and Damith Herath) -- Chapter 9 - Lost in space! Localisation and Mapping (Damith Herath) -- Chapter 10 - How to manipulate? Kinematics, dynamics and architecture of robot arms (Bruno Belzile and David St-Onge) -- Chapter 11 - Get together! Multi-robot systems: bio-inspired concepts and deployment challenges (Vivek Shankar Varadharajan and Giovanni Beltrame) -- Chapter 12 - The Embedded design process: CAD/CAM and prototyping (Eddi Pianca) -- PART III: Interaction Design -- Chapter 13 - Social robots: Principles of interaction design and user studies (Janie Busby Grant & Damith Herath) -- Chapter 14 - Safety first: On the safe deployment of robotic systems (Bruno Belzile and David St-Onge) -- Chapter 15 - Managing the world complexity: from linear regression to deep learning (Yann Bouteiller) -- Chapter 16 - Robot ethics: Ethical design considerations (Dylan Cawthorne) -- Chapter 17 - Robot Hexapod Build Labs (David Hinwood and Damith Herath) -- Chapter 18 - ROS Mobile Manipulator labs (David St-Onge, Corentin Boucher and Bruno Belzile)
Includes index.
Keywords: Robotics; Robots -- Programming; Python (Computer program language); Electronic books